2022
DOI: 10.1002/advs.202200082
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Dipole Orientation and Symmetry Breaking with Mixed‐Dimensional Heterostructures

Abstract: Engineering of the dipole and the symmetry of materials plays an important role in fundamental research and technical applications. Here, a novel morphological manipulation strategy to engineer the dipole orientation and symmetry of 2D layered materials by integrating them with 1D nanowires (NWs) is reported. This 2D InSe -1D AlGaAs NW heterostructure example shows that the in-plane dipole moments in InSe can be engineered in the mixed-dimensional heterostructure to significantly enhance linear and nonlinear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The power exponent between the SHG intensity and excitation power was fitted as 1.97, nearly a quadratic dependence (Figure d). These results confirm the second-order NLO process and are in line with the prediction of the electric-dipole theory. As discussed above, PdBr 2 belongs to the centrosymmetric point group C 2 h . Due to the presence of central inversion symmetry between adjacent layers, it is expected that PdBr 2 would exhibit a negligible second-order susceptibility, resulting in the inhibition of SHG signals.…”
Section: Resultssupporting
confidence: 87%
“…The power exponent between the SHG intensity and excitation power was fitted as 1.97, nearly a quadratic dependence (Figure d). These results confirm the second-order NLO process and are in line with the prediction of the electric-dipole theory. As discussed above, PdBr 2 belongs to the centrosymmetric point group C 2 h . Due to the presence of central inversion symmetry between adjacent layers, it is expected that PdBr 2 would exhibit a negligible second-order susceptibility, resulting in the inhibition of SHG signals.…”
Section: Resultssupporting
confidence: 87%
“…[62,87,170,[234][235][236] Apart from the above-mentioned homostructures, recent works have also revealed their tunability and enhancement of SHG properties in vdW heterostructures. [82,88,221,224,[240][241][242][243][244] By stacking two different 2D crystals on top of each other or twisting them with designed angles without the constrain of lattice matching, various heterostructures have been studied during the latest decade, such as GaSe-InSe, [88] MoTe 2 -WSe 2 , [240] MoS 2 -graphene, [221] ReS 2 -graphene, [244] etc. Zhang et al observed emergent SHG in vdW stacking of centrosymmetric bilayer MoS 2 and monolayer graphene (Figure 3d).…”
Section: Vdw Engineeringmentioning
confidence: 99%
“…Since the exfoliation of graphene, the unique electrical, optical, magnetic, and topological properties of two-dimensional (2D) van der Waals (vdW) materials have attracted significant interest and largely transformed the landscape of fundamental research and technological advances in physics, material sciences, and chemistry. Remarkably, the dangling-bond-free nature of 2D materials enables them to be integrated with non-2D materials (e.g., 0-, 1-, or 3-dimensional materials) through noncovalent interactions to form emerging mixed-dimensional vdW heterostructures. These heterostructures can combine the synergistic advantages of different dimensional materials, thus providing a more favorable platform than bare 2D materials for numerous advanced applications ranging from on-chip photodetectors to nanolasers. …”
Section: Introductionmentioning
confidence: 99%